Negative Concord in Some Selected Quranic Verses: A Contrastive Study - Saja Mohammed Magrood , Researcher (lark, 2022)
Because it compares Negative concord in Arabic and English to determine the similarities and differences between the two languages, the current study is a descriptive, analytical, and contrastive one. Since negative concord is a phenomenon that has garnered a lot of interest in recent research, the study attempts to describe, analyze, and compare negative concord in English and Arabic. Two or more syntactic negations that are in agreement semantically are referred to as negative concord. In order to demonstrate how Negative concord is dialectal in English and how it occurs in both standard and non-standard Arabic, this study compares the occurrence of Negative concord in vernacular or non-standard English to that of Modern Standard Arabic (MSA) and vernacular varieties in Arabic.
Keywords: Keywords: contrastive, dialectal, negative concord, selected verses, vernacular